2022
DOI: 10.1111/tpj.15784
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth dynamics in two types of apical meristems in fern gametophytes

Abstract: SUMMARY In contrast to seed plants, the gametophytes of seed‐free plants develop pluripotent meristems, which promote and sustain their independent growth and development. To date, the cellular basis of meristem development in gametophytes of seed‐free ferns remains largely unknown. In this study, we used Woodsia obtusa, the blunt‐lobe cliff fern, to quantitatively determine cell growth dynamics in two different types of apical meristems – the apical initial centered meristem and the multicellular apical meris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 46 publications
(117 reference statements)
0
33
0
Order By: Relevance
“…Computational segmentation and quantification results further demonstrated that active division and expansion of the AC and its immediate progenies contributed to notch formation and prothallus expansion in S. chinensis gametophytes [ 24 ]. The characterizations of ACs in different fern gametophytes altogether [ 14 , 21 , 22 , 23 , 24 , 52 , 54 , 55 ] suggest that the activity of wedge-shaped ACs in gametophytes likely independently evolved in fern taxa [ 24 ].…”
Section: Apical Cells: Maintenance Proliferation and Disappearancementioning
confidence: 99%
See 4 more Smart Citations
“…Computational segmentation and quantification results further demonstrated that active division and expansion of the AC and its immediate progenies contributed to notch formation and prothallus expansion in S. chinensis gametophytes [ 24 ]. The characterizations of ACs in different fern gametophytes altogether [ 14 , 21 , 22 , 23 , 24 , 52 , 54 , 55 ] suggest that the activity of wedge-shaped ACs in gametophytes likely independently evolved in fern taxa [ 24 ].…”
Section: Apical Cells: Maintenance Proliferation and Disappearancementioning
confidence: 99%
“…Independent studies all demonstrated that the conserved oblique division in the AC resulted in one new wedge-shaped apical cell and one adjacent trapezoid-shaped cell, leading to the renewal of the ACs in fern gametophytes ( Figure 2 B) [ 21 , 22 , 24 ]. By contrast, in the gametophytes of many fern species, including Woodsia obtusa and Lygodium japonicum , the oblique division is only maintained for a limited time [ 21 , 23 ]. After only a few rounds of oblique division, the AC undergoes the division in a periclinal orientation, resulting in one trapezoid-shaped daughter cell outside and one triangular daughter cell inside ( Figure 2 C) [ 23 ].…”
Section: Apical Cells: Maintenance Proliferation and Disappearancementioning
confidence: 99%
See 3 more Smart Citations